Clinical Outcome and Wound Healing following Carpal Tunnel Decompression: A Comparison of Two Common Suture Materials. (6th August 2014) - MacFarlane, Robert J.; Donnelly, Thomas D.; Khan, Yousaf; Morapudi, Syam; Waseem, Mohammad; Fischer, Jochen
Abstract : Introduction . Debate exists amongst surgeons regarding the ideal suture material for skin closure in carpal tunnel decompression (CTD). This study compares wound related complications, patient satisfaction, and functional outcome following open carpal tunnel decompression in patients undergoing wound closure with either of two common absorbable and nonabsorbable suture types. Materials and Methods . 53 patients underwent CTD with either 4/0 polypropylene (ProleneTM, n = 28) or 4/0 polyglactin (Vicryl RapideTM, n = 25) for skin closure. QuickDASH, VAS satisfaction scores, and Southampton wound scores were assessed preoperatively and at 2 and 6 weeks postoperatively. Results . At 6 weeks the mean QuickDASH scores postoperatively were 18.54 and 17.70 for absorbable and nonabsorbable sutures, respectively, (P = 0.86). The mean VAS scores were 0.61 and 0.42 (P = 0.91), respectively. All patients achieved a Southampton wound score of 0 by 6 weeks except one, who achieved 1C in the nonabsorbable group, equivalent to mild erythema. There were no complications in either group. Conclusion . Both suture types are safe and effective materials for CTD, and we recommend surgeons to choose according to personal preference, handling properties, and resources available for suture removal.